Guidelines on Vehicle Overload Control in Eastern and Southern Africa - Pinard, Michael lan (World Bank, Washington, DC, 2014)
Heavy goods vehicle overloading is a serious problem across much of Sub-Saharan Africa. Such overloading not only significantly accelerates the rate of deterioration of road pavements but, when coupled with inadequate funding for road maintenance, it contributes significantly to poor road conditions and high transport costs. The indicative cost of overloading in East and Southern Africa has been estimated at more than US$4 billion per annum. This exceeds the amounts being spent on road rehabilitation. Therefore, unless the problem is tackled head on, it will negate the expected benefits from the huge amounts of resources that countries and donors are investing into improved road infrastructure across the continent. The cost associated with vehicle overloading can be avoided through effective control measures. The guidelines presented here are an important contribution to tackling the challenge of vehicle overloading in East and Southern Africa. The solutions should be relevant to other parts of Africa as well as to other developing regions of the world. The document makes two facts very apparent: there are in various countries numerous examples of effective overload control strategies which have shown positive results and vehicle axle load control is a multidisciplinary and multi-stakeholder effort. In other words, vehicle overload control is not an intractable problem and can be tackled effectively with benefits to all road users and to society at large.